2003
DOI: 10.1186/1478-4491-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Human resources for health policies: a critical component in health policies

Abstract: In the last few years, increasing attention has been paid to the development of health policies. But side by side with the presumed benefits of policy, many analysts share the opinion that a major drawback of health policies is their failure to make room for issues of human resources. Current approaches in human resources suggest a number of weaknesses: a reactive, ad hoc attitude towards problems of human resources; dispersal of accountability within human resources management (HRM); a limited notion of perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
264
0
41

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(307 citation statements)
references
References 36 publications
2
264
0
41
Order By: Relevance
“…A modernized policy on health workforce performance, including an absence-management policy to address filling in for workers away on study leave, could address problems of supply and working conditions related to workforce retention. 17 Given the sizable gap between salaries in Uganda and those abroad (salaries in the United Kingdom are approximately thirteen times higher), it seems critically important to begin to address compensation factors to avoid turnover and reduce incentives to leave the health sector or the country. 18 Ugandan Catholic hospital data on turnover (obtained and analyzed separately) revealed that low salary was the leading reason for individuals' leaving their jobs in 2005.…”
mentioning
confidence: 99%
“…A modernized policy on health workforce performance, including an absence-management policy to address filling in for workers away on study leave, could address problems of supply and working conditions related to workforce retention. 17 Given the sizable gap between salaries in Uganda and those abroad (salaries in the United Kingdom are approximately thirteen times higher), it seems critically important to begin to address compensation factors to avoid turnover and reduce incentives to leave the health sector or the country. 18 Ugandan Catholic hospital data on turnover (obtained and analyzed separately) revealed that low salary was the leading reason for individuals' leaving their jobs in 2005.…”
mentioning
confidence: 99%
“…Among this NGO clinic referred the cases, identification and management of sepsis (NCD5), identification and management of omphalitis (NCD6), identification and management of LBW babies (refer <1, 800 (NCD7), identification and management of neonatal jaundice (NCD8) and Union health and family welfare center referred the cases-identification and management of neonatal jaundice (NCD8), identification and management of breastfeeding problems (NCD9) [7]. But Upazilla health complex able to serve all of services for newborn care after delivery shows in beside Figure 4C.…”
Section: Resultsmentioning
confidence: 99%
“…10 At the same time, considering the effi cient use of human resources within the context of institutional capacity should be an essential part of the reform process; this includes the reorientation of education, the training and practice of professionals and the study of ways to retain and strengthen the capacity of human resources for health.…”
Section: Human Resources Policy and Reformsmentioning
confidence: 99%